Use Of Imagery And Metaphor In Aravind Adiga’s The White Tiger - Kasbekar, Sushama (Bina Nusantara University, 2011)
This paper focuses on the use of imagery and metaphors in Arvind Adiga’s The White Tiger (2008). The writer deliberately and skillfully uses animal imagery and other kinds of metaphors to highlight the intrinsic values of his characters and present themes and characters vividly. This paper highlights how this imagery and metaphor has been used by the writer to bring out the thematic rich and poor divide or the servitude of the poor and overbearing opulence of the rich. The metaphors give added value to the themes and the characters and provide an immediate verbal picture.